A GIS Based Walkability Measurement within the Built Environment of Khulna City, Bangladesh (Journal of Bangladesh Institute of Planners, 2015)
Walking has become an intense topic in the field of urban planning, transportation planning and urban health sector. To evaluate the walking pattern of a city, first walkability is needed to be assessed. The effects of built environment on walking has been drawn out in separate walkability assessment studies worldwide. But walkability assessment in the context of a developing country is not too common, especially in Bangladesh it is unprecedented. This study proposesa method of developing walkability index model for Khulna City. The study can disseminate walkability scores for each ward and can find out the hierarchy of different wards according to their ability of promoting more walking. The walkability index equation has been generated comparing two model diagnostics i.e. Ordinary Least Squares (OLS) and Geographically Weighted Regression (GWR). By comparing OLS and GWR, the most suitable model was found from GWR. By using this equation, scores of walkability index for each ward was calculated and three levels of walkability was found i.e. High, Medium and Low. By analyzing residents’ perception on reasons of walking, safety of walking, obstacles for walking and satisfactory level of footpaths, a different score and rank was calculated. The spearman’s rank correlation coefficient was found significant (p=0.81) which indicates that the results found from walkability model index is good.Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 145-158